Leo Africanus' contribution to a Latin translation of the Qur'ān: A case study of intellectual activity after conversion - Starczewska, Katarzyna K. (Studi e materiali di storia delle religioni, 2018)
The aim of this contribution is two-fold: to present, albeit briefly, the history of Latin translations of the Qur'ān, emphasising the cases in which Church officials commissioned the translations to Muslims or Muslim converts; and secondly, to observe a particular case of a Qur'anic translation, which was modified and improved by Leo Africanus (also known as Leo Granatinus or Yūhannā al-Asad, formerly al-Hasan al-Wazzān). The translations which, as far as we know, can be described as cases of interfaith collaborations are the first one elaborated by Robert of Ketton (1142-1143), the lost text boosted by Juan of Segovia (1456) and the interpretation commissioned by Egidio da Viterbo (1518, 1525) to which I will devote the second part of this study. (English)